Arrb2 causes hepatic lipid metabolism disorder via AMPK pathway based on metabolomics in alcoholic fatty liver. Issue 10 (28th May 2021) - Sun, Ying-Yin; Wu, Dong-Qing; Yin, Na-Na; Yang, Lei; Chen, Xin; Li, Hai-Di; Li, Xiao-Feng; Huang, Cheng; Meng, Xiao-Ming; Wang, Hua; Li, Jun
Abstract: Background and aims: Alcoholic fatty liver (AFL) is an early form of alcoholic liver disease (ALD) that usually manifests as lipid synthesis abnormalities in hepatocytes. β-arrestin2 (Arrb2) is involved in multiple biological processes. The present study aimed to explore the role of Arrb2 in the regulation of lipid metabolism in AFL and the underlying mechanism and identify potential targets for the treatment of AFL. Methods: The expression of Arrb2 was detected in liver tissues obtained from AFL patients and Gao-binge AFL model mice. In addition, we specifically knocked down Arrb2 in AFL mouse liver in vivo and used Arrb2-siRNA or pEX3-Arrb2 to silence or overexpress Arrb2 in AML-12 cells in vitro to explore the functional role and underlying regulatory mechanism of Arrb2 in AFL. Finally, we investigated whether Arrb2 could cause changes in hepatic lipid metabolites, thereby leading to dysregulation of lipid metabolism based on liquid chromatography-mass spectrometry (LC-MS) analysis. Results: Arrb2 was up-regulated in the livers of AFL patients and AFL mice. The in vivo and in vitro results confirmed that Arrb2 could induce lipid accumulation and metabolism disorders. Mechanistically, Arrb2 induced hepatic metabolism disorder via AMP-activated protein kinase (AMPK) pathway. The results of LC-MS analysis revealed that hepatic lipid metabolites with the most significant differences were primary bile acids. Conclusions: Arrb2 induces hepatic lipid metabolism disorders via AMPK pathway in AFL. On one hand, Arrb2 increases fatty acid synthesis. On the other hand, Arrb2 could increase the cholesterol synthesis, thereby leading to the up-regulation of primary bile acid levels.